Study on species diversity of ancient trees in Zhejiang Province - DU Qun; CHEN Zheng-hai; LIU An-xing; ZHUGE Gang (浙江大学学报. 农业与生命科学版, 2005)
According to investigation in 2002, there are 21.37×104 ancient trees, which belongs to 459 species (including varieties), 196 genera, 73 families in Zhejiang Province. The present situation of species diversity was analyzed in this paper. It is showed that ancient trees in Zhejiang Province have many characteristics, such as abundant species, rich in rare plants, old origin, many exotic species and complicated distribution types.